On difference and doubt as tools for critical engagement with public health. Issue 3 (27th May 2017) - Will, Catherine M.
Abstract: This paper argues that critical public health should reengage with public health as practice by drawing on versions of Science and Technology Studies (STS) that 'de-centre the human' and by seeking alternative forms of critique to work inspired by Foucault. Based on close reading of work by Annemarie Mol, John Law, Vicky Singleton and others, I demonstrate that these authors pursue a conversation with Foucault but suggest new approaches to studying contemporary public health work in different settings. Proposing that we 'doubt' both the unity of public health and its effects, I argue that this version of STS opens up a space to recognise multiplicity; to avoid idealising what is being criticised; and to celebrate or care for public health practices as part of critique. Finally I oppose the view that considering technologies, materials and microbes leads to micro-level analysis or political neutrality, and suggest that it allows us to reframe studies of public health to account for inequalities and to draw attention to weak or retreating states, active markets and the entangled relations of humans and non-humans across the world.